Sosialisasi Dan Identifikasi Bahaya Pestisida Dan Cara Penggunaan Yang Aman Bagi Petani Dalam Budidaya Tanaman Pangan Di Moyo Utara - Rafi’ah Rafi’ah; Iga Maliga; Ana Lestari; Herni Hasifah (Universitas Katolik Widya Karya Malang, 2023)
Pesticides are chemical substances used in agriculture to combat pests and diseases in plants. Improper use of pesticides can pose hazards to human health and the environment. The purpose of this community service is to identify pesticide hazards and provide education to farmers in North Moyo on the safe use of pesticides in crop cultivation. The methods to be employed in this community service include conducting surveys and identification of pesticide use practices in North Moyo, as well as raising awareness about the dangers of pesticides and safe usage methods. The outcome of this community service is that farmers in North Moyo will have a better understanding of the hazards of pesticides and safe usage practices, thereby minimizing health and environmental risks in crop cultivation.